EVALUATION OF HERBICIDES FOR POTATO SPROUT SUPPRESSION ACTIVITY (Biological Sciences - PJSIR, 2002)
Herbicides incl uding barban , embark, diuron, prometryne , simazine, atrazine, destmetryne, asulam, monuron and linuron are screened for potato sprout suppression activity. A potato sprout suppressant will be expected  to  inhibit  growth  of cress root, tomato shoot or potato tissue callus. It is observed that only embark shows pronounced inhibition of callu s growth. Embark was found  to  be  effective  as a  potato  sprout  suppressant  at high  application  rate  of 500mgkg·1.